Principals’ Time Management and School Effectiveness in Public Secondary Schools in Kwara State, Nigeria - Adeseko Sunday OLAIFA; Raimi OBA-SULEIMAN; Seyi ARE; Olubunmi Olufunke OSHIN; Moses Adeleke ADEOYE (Departement of Psychology, Faculty of Education, Universitas Negeri Semarang, 2023)
Principals’ Time Management and School Effectiveness have a positive impact on public secondary schools in Kwara state, Nigeria. The study examines Principals’ Time Management and School Effectiveness in Public Secondary Schools in Kwara State, Nigeria. A descriptive research design of correlation type was adopted for this study. The population of the study was made up of 15,416 teachers and 397 principals in all the 397 public secondary schools in the three senatorial districts that constitute Kwara State (Kwara Central, Kwara North and Kwara South) using a Research-Advisor sample size. The researcher instrument used was titled Principals’ Time Management Questionnaire (PTMQ) and School Effectiveness Questionnaire (SEQ) was used to collect relevant data from the respondents. The data gathered were statistically analyzed using Mean, Standard Deviation and Pearson Product Moment Correlation (PPMC). The result obtained from the respondents revealed that time planning has a positive impact on schools ‘effectiveness as most principals have adequate time planning for the teachers in the school to enhance their teaching roles in secondary schools in Kwara state, Nigeria. It was concluded that the principal time control, time planning, time evaluation and time utilization have a positive impact on school effectiveness in public secondary schools in Kwara state, Nigeria. Keywords: Time Management, School Effectiveness, Principals’ Time Control